Electrochemical Oxidation of Methylene Blue Using Carbon Electrode from Battery Waste - Hakim, Supwatul; Tety Wahyuningsih Manurung; Dwi Hermayantingsih; Mokhamat Ariefin (Helium: Journal of Science and Applied Chemistry, 2024)
Methylene blue in the environment can disrupt the ecosystem because it does not decompose easily. Therefore, this research aims to oxidize methylene blue using an electrochemical oxidation method. The electrochemical oxidation of methylene blue was successfully carried out using carbon electrodes from battery waste. The influence of pH value and electrolysis time was successfully investigated using a UV-Vis spectrophotometer, and the decreased absorbance (DA(%)) was also analyzed. Based on the results, the optimum pH for electrochemical oxidation with a carbon electrode is at pH 1. It was possible to reduce the absorbance at this pH with a decreased absorbance of 56%. There was a decrease in absorption in the UV and visible regions. The optimum time for methylene blue electrochemical oxidation was 15 minutes, with a decreased absorbance percentage at 100%. The electrochemical oxidation method is simple and easy to use. This finding can be an excellent and effective wastewater treatment method.